Environmental Agenda: Risks of Maintaining the Status Quo - Agaev Murat; Shardan Saida; Magomaev Tamirlan (BIO Web of Conferences, 2023)
“Turn to nature” and the inextricable connection between nature and man, ensuring the well-being, security and development of the latter, should become an integral element of Russian identity and national idea, its mission for itself and for the world. The concepts of “nature” and the Motherland should become inseparable. At the same time, the inseparable connection between the protection of nature and human well-being, the development of human capital can become one of the most important tools for the internal consolidation of the country, an idea that unites the elite (regardless of political preferences) and society.